Portable thermoelectric power generation based on catalytic combustor for low power electronic equipment. (1st April 2018) - Fanciulli, C.; Abedi, H.; Merotto, L.; Dondè, R.; De Iuliis, S.; Passaretti, F.
Highlights: New TEG based on catalytic combustor is developed with a volume close to AA battery. The system is designed to be safe, accessible for portable use as electronic supplier. Our solution shows an alternative for low power supply open to further improvements. Characterization procedure is defined allowing deep understanding of the processes. Abstract: In recent years, the portable technology is receiving a great interest and significant improvement due to the progresses in electronic technology development and energy storage solutions. The decrease in power requirements for working energy systems, due to the increased efficiency and to the reduction in components size, opens the access to new solutions for power supplying. In particular, alternative backup systems for battery charging or replacement could be designed taking advantage of unconventional technologies. It is the case of small photovoltaic portable panels or fuel cells technology: in these solutions different sources are used to produce limited electrical powers required to keep devices on. In this paper, a thermoelectric solution for the power generation has been considered: the generator has been designed and assembled starting from a catalytic combustor. Catalytic combustion allows safe control of the processes, and the choice of a hydrocarbon fuel ensures the power availability and a fast recharge. The size of the system is set to fit a volume close to the one of AA batteries. The electrical power output obtained is close to 1 W with a cold side temperature below 40 °C. The limited values of these physical parameters allow obtaining a portable and safe device. The generator has been fully characterized in different ranges of fuel flow rates and the performances have been thoroughly analysed for processes optimization and efficiency improvement.